Application Of Green Entrepreneurship Towards Economic Improvement (Literature Study) - Cahyati, Suci; Chairia, Chairia; Putri, Hidayatna; Romadhona, M.Rifqi (Junal Ilmu Manajemen, 2024)
Green entrepreneurship plays an important role in economic transformation towards a sustainable development model. This study explains the application of green entrepreneurship and its impact on economic improvement. The adoption of environmentally friendly business practices, such as renewable energy, waste management and eco-friendly products, has opened up new opportunities for sustainable economic growth. Through the creation of new jobs, improved resource efficiency, and stimulation of innovation, green entrepreneurship has helped improve the competitiveness of firms in the global market. Government policy support, both in the form of fiscal incentives and supportive regulations, has accelerated the adoption of green business practices. The positive influence of green entrepreneurship is also reflected in the consumption of consumers who increasingly prefer sustainable products and services. This creates new markets and drives economic growth in sustainable sectors, such as renewable energy and green technology. The importance of partnerships and collaboration between the private sector, government and non-profit organizations is also highlighted in this study. This collaboration accelerates the development of new sustainability-focused industries and creates more efficient supply chains. By considering environmental risks and building businesses that are resilient to climate change, green entrepreneurship has proven that environmentally responsible business practices can positively contribute to long-term economic growth.